Agent‐based modeling to integrate elements from different disciplines for ambitious climate policy. (27th November 2022) - Savin, Ivan; Creutzig, Felix; Filatova, Tatiana; Foramitti, Joël; Konc, Théo; Niamir, Leila; Safarzynska, Karolina; van den Bergh, Jeroen
Abstract: Ambitious climate mitigation policies face social and political resistance. One reason is that existing policies insufficiently capture the diversity of relevant insights from the social sciences about potential policy outcomes. We argue that agent‐based models can serve as a powerful tool for integration of elements from different disciplines. Having such a common platform will enable a more complete assessment of climate policies, in terms of criteria like effectiveness, equity and public support. This article is categorized under: Climate Models and Modeling > Knowledge Generation with Models The Carbon Economy and Climate Mitigation > Policies, Instruments, Lifestyles, Behavior Policy and Governance > Multilevel and Transnational Climate Change Governance Abstract : Using ABMs to integrate elements from different disciplines for ambitious climate policy